Selective deprotection strategies to N-(alpha-methylbenzyl)-beta-amino esters and derived beta lactams - Davies, S; Ichihara, O (1998)
A variety of N,N-diprotected β-amino esters, prepared by highly diastereoselective conjugate addition of chiral lithium amides, were selectively mono-deprotected under either reductive (hydrogenolysis) or oxidative (DDQ or CAN) conditions. Combined with these deprotection methods, lithium (α-methylbenzyl)(3,4-dimethoxybenzyl) amide 2 can be used as an efficient differentially protected chiral ammonia equivalent for the asymmetric synthesis of β-amino acid and β-lactam derivatives.